PENGARUH MINIMALISASI PAJAK, MEKANISME BONUS KEPEMILIKAN ASING TERHADAP TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR MULTINASIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Juarsa Badri; Henryanto Abaharis; Alfian Alfian; Yosep Eka Putra; Romi Susanto (JURNAL ILMIAH EDUNOMIKA, 2023)
Globalization in the economic and business fields has led to economic development that knows no boundaries between countries. Many transactions between companies are increasing, both between domestic and foreign companies. The flow of goods, services, capital (investment), and labor is easier and smoother between countries. This research was conducted with the aim of obtaining empirical evidence regarding the effect of tax minimization, foreign ownership, and bonuses on transfer pricing. This study used 12 samples of multinational manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Based on the test results, the following conclusions are obtained: First, the test results show that tax minimization (X1) partially affects transfer pricing (Y), this is evidenced by using the t test with a t value of 2.428 ≥ t table 2.042 with a significance of 0.022 ≤ 0.05. Second The test results show that partially foreign ownership (X2) has no effect on transfer pricing (Y). This is evidenced by using the t test with a t table value of 1.09898 t table 2.042 with a significance of 0.281 ≥ 0.05. Third. The test results show that the bonus (X3) partially has no effect on transfer pricing (Y), this is evidenced by using the t test with the t value 1.293 29 t table 2.042 with a significance of 0.206 ≥ 0.05.